Aplikasi Pelayanan Pasien Di Klinik Dokter Umum Berbasis Website - Hasyim, Muhammad Nur; , Umi Fadlillah, ST. MEng (2015)
Clinic dr.Suci Astuti website provide convenience to the patient to make a reservation queue number. Moreover, this website also allows employees to log the patient and recording the result of medical records. Before this website, clinic dr.Suci Astuti doing all patient data and record-keeping by hand, this make trouble finding a clinic employee medical records already accumulated a lot. This website, will allow employees to search medical records and also recording data of patients who want treatment. The website building is using PHP, MySQL and the user interface using HTML, CSS, Bootstrap, dan JQuery and use the application sublime text, Adobe Photoshop, Google Chrome, DBDesigner, dan Xampp. The system was tested using questionnaires to patient clinic and employee. Results of the questionnaire showed patients with this website can help advance clinical activity in terms of clinical publications, because the percentage to interpretation reached 78,6% It was the highest percentage. While in terms of getting information about clinical presentation lowest interpretation that only 53,3 %. For admins can help clinic staff in a search of medical records and also to access the data it can be seen in the results of recapitulation admin questionnaire which showed the results of 100 %, while the rest of the statement to get 80 % in the recapitulation questionnaire admin